2020
DOI: 10.1177/2040620720914489
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of the JAK/STAT signaling pathway in graft-versus-host disease

Abstract: Allogeneic hematopoietic transplantation (allo-HCT) is a curative therapy for a variety of hematologic malignancies, primarily through immune-mediated clearance of malignant cells. This graft- versus-leukemia (GvL) effect is mediated by alloreactive donor T-cells against recipient malignant cells. Unfortunately, graft versus host disease is a potentially lethal complication of this procedure, also mediated by alloreactive donor T-cells against recipient normal tissues. Graft- versus-host disease (GVHD) remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
(119 reference statements)
1
23
0
Order By: Relevance
“…A recent phase 3 study of JAK1 inhibitor Itacitinib on aGVHD showed the overall response rates in Itacitinib and placebo groups were 74% and 66% ( P = 0.0782), respectively, and 6-month NRM also did not favor Itacitinib (NCT03139604), which suggested that balanced inhibition of JAK1/JAK2 is vital in treatment of GVHD 10 , 41 . The JAK1/2 inhibitor Ruxolitinib, the most common used JAK inhibitor in clinical practice, has been proven to be effective in the treatment of patients with aGVHD and has been approved by FDA 14 , 15 . We found that the novel JAK inhibitor SHR0302 has a lower half maximal inhibitory concentration (IC50) for JAK1 and JAK2 than Ruxolitinib, which suggested that SHR0302 might have stronger effects than Ruxolitinib on GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase 3 study of JAK1 inhibitor Itacitinib on aGVHD showed the overall response rates in Itacitinib and placebo groups were 74% and 66% ( P = 0.0782), respectively, and 6-month NRM also did not favor Itacitinib (NCT03139604), which suggested that balanced inhibition of JAK1/JAK2 is vital in treatment of GVHD 10 , 41 . The JAK1/2 inhibitor Ruxolitinib, the most common used JAK inhibitor in clinical practice, has been proven to be effective in the treatment of patients with aGVHD and has been approved by FDA 14 , 15 . We found that the novel JAK inhibitor SHR0302 has a lower half maximal inhibitory concentration (IC50) for JAK1 and JAK2 than Ruxolitinib, which suggested that SHR0302 might have stronger effects than Ruxolitinib on GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated the therapeutic effects of JAK1/2 inhibitor Ruxolitinib for patients with acute and chronic GVHD 12 14 . The clinical trials of another JAK1/2 inhibitor Baricitinib for acute or chronic GVHD is ongoing (NCT04131738, NCT02759731) 15 . Recently, a JAK1 inhibitor Itacitinib was demonstrated to have a good response rate for acute GVHD in clinical trials 16 , 17 and its effects on chronic GVHD remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ruxolitinib is an inhibitor of Janus kinase 1 (JAK1) and JAK2, currently FDA‐approved for treatment of myeloproliferative neoplasms and steroid‐refractory acute GVHD 39 . Through inhibition of the JAK/STAT (signal transducers and activators of transcription) pathway, ruxolitinib induces numerous downstream immunomodulatory effects on immune cell development and also promotes an anti‐inflammatory environment through changes in the cytokine milieu 40 …”
Section: Second‐line Therapymentioning
confidence: 99%
“…39 Through inhibition of the JAK/STAT (signal transducers and activators of transcription) pathway, ruxolitinib induces numerous downstream immunomodulatory effects on immune cell development and also promotes an antiinflammatory environment through changes in the cytokine milieu. 40 Three multicentre retrospective studies reported on ruxolitinib use for cGVHD. ORR across these studies ranged between 57Á1% and 100%, with CR rates of 3-7Á3%.…”
Section: Ruxolitinibmentioning
confidence: 99%
“…They inhibit the activation and proliferation of T‐lymphocytes which blocks growth factor‐induced transduction signals that mediate cellular division in response to alloantigens 8 . Sirolimus has been used in the prevention and treatment of GVHD after allo‐HCT 9 . Its safety and efficacy have been compared in several trials to tacrolimus and were found to provide similar GVHD‐free survival 10,11 …”
Section: Introductionmentioning
confidence: 99%